Inside Document Models: Role of Source Attributes in Readers' Integration of Multiple Text Contents. Issue 1 (2nd January 2021) - Rouet, Jean-François; Saux, Gaston; Ros, Christine; Stadtler, Marc; Vibert, Nicolas; Britt, M. Anne
ABSTRACT: Text comprehension involves the ability to understand how texts relate to the situation they describe and to each other (i.e., a Document model). Research into Document models has emphasized the role of information sources in structuring readers' mental models of situations. The present article reviews research on source comprehension and examines new hypotheses regarding source encoding during text comprehension. Two experiments examined college students' evaluation and recognition of two embedded sources as a function of the consistency of their statements (Experiments 1 and 2) and the demands of the reading task (Experiment 2). Sources were introduced either with a knowledge feature (e.g., how the source knew what they knew) or a control feature. Readers were more likely to select the knowledgeable source as more competent and to justify their selection by referring to the knowledge feature (Experiment 1). Experiment 2 found that readers' preference for knowledgeable sources was stronger when the content statements were discrepant. Preference for knowledgeable sources was also stronger when the task focused on source knowledge, as compared to a control evaluation task or a baseline reading task. The source knowledge evaluation task distinctively enhanced participants' integration of the source designations with their respective statements, as compared to the control and baseline conditions. Results are discussed in light of current theories of single and multiple document comprehension.